A continuous valence band through NO orbital hybridization in NTiO2 and its induced full visible-light absorption for photocatalytic hydrogen production. (5th February 2019) - Sun, Shuchao; Chi, Qianqian; Zhou, Han; Ye, Wei; Zhu, Genping; Gao, Peng
Abstract: Photocatalytic hydrogen production represents an effective approach for solar energy conversion, which can greatly ease the current energy crisis. Herein, we report a successful NO orbital hybridization in N-doped TiO2 nanotube, the absorption wavelength is greatly red-shifted to visible light (from 400 to 800 nm) with large absorbance. The doping N element can partially replace the oxygen sites in TiO2 lattice to form NTiN bonds. The hybridization effect of N 2p and O 2p makes a continuous valence band and the position up-shift from 1.99 to 1.67 eV, the band gap is subsequently narrowed from 3.21 to 2.77 eV for 1.85-NTiO2 nanotube, which has been confirmed by ultraviolet–visible diffuse reflectance spectra and X-ray photoelectron spectroscopy valence band spectra. Benefiting from the enhanced visible light absorption ability and ultrathin shell feature, 1.85-NTiO2 nanotube exhibits exciting photocatalytic hydrogen evolution performance with a rate of 10870 μmol h −1 g −1 under the selected visible light irradiation (λ > 400 nm). This work demonstrates an alternative strategy for tuning visible light absorption ability by doping for wide-band-gap semiconductors in photocatalysts design, and the philosophy can also be extended to other photocatalytic systems. Graphical abstract: NO Orbital Hybridization induced full visible-light absorption was achieved in N-doped TiO2 nanotube. 1.85-NTiO2 nanotube displays enhanced photocatalytic hydrogen evolution performance with a rate of 10870 μmol h −1 g −1 . Highlights: NO orbit hybridization was achieved for NTiO2 nanotube. NTiO2 nanotube achieves full visible-light absorption. The ultrathin TiO2 shell boosts active sites. Ultrahigh hydrogen production rate was realized.